Diverse applicability of color-tunable synthesized calcium molybdate nanoparticles - Jae Yong Jung; Jin Young Park; Woo Tae Hong; Jung Sik Joo; Won Kyo Jung; Hyun Kyoung Yang (Journal of Science: Advanced Materials and Devices, 2024)
Crystalline CaMoO4 NPs were synthesized using a solvothermal method in an autoclave. The synthesized CaMoO4 could detect a signal in the main peak of (112) phase in the XRD pattern. It emits an absorption spectrum in the UV region and an emission spectrum wide range of 380–680 nm. Single-doped Tb3+ ions and Eu3+ ions were used as luminescent materially.. To reproduce the various colors, the amount of Tb3+ ions added was fixed, and the amount of Eu3+ ions was increased to synthesize them. When excited by UV light, the synthesized CaMoO4: [Eu3+]/[Tb3+] displayed various colors from green to yellow, orange, and red. Light-emitting powders of various colors were mixed with polydimethylsiloxane (PDMS) to create a flexible composite sheet that could be folded, rolled, and applied to UV-LED to create unique colors. In addition, it was possible to identify fingerprints on a glass substrate. It was proposed that this could be applied to anti-counterfeiting by manufacturing a solution that could be identified only when applied to banknotes and irradiated with a UV lamp.